The Impact of the PBL Model on Senior High School Student Learning Outcomes Using Google Classroom - RIZKI Harahap; Albinus Silalahi; Zainuddin Muchtar (Universitas Lampung, 2021)
Abstract: The Impact of the PBL Model on Senior High School Student Learning Outcomes Using Google Classroom. This study aims to determine the effect of the problem based learning model with the help of google classroom media on the learning outcomes of high school students on the subject of oxidation-reduction reactions at SMAN 1 Siantar. This type of research is an experimental study with a pretest-posttest control design. The data collection of student learning outcomes was obtained from the pretest and posttest scores. This study resulted in the average data of student learning outcomes from the posttest in the experimental class that was greater than the control class, namely 62 and 50. Data analysis used the T-Test test which resulted in a significance value of learning outcomes less than 0.05, namely 0.003. Based on this analysis, it can be concluded that learning using the PBL model with the help of google classroom media has a significant effect on senior high school student learning outcomes on oxidation-reduction material at SMAN 1 Siantar.